Chinese international students’ mental health in Western universities: a scoping review - Jianyiwen Zhao; Ke Shi; Phoebe Barnett; Stephen Pilling; Peter Fonagy (BMC Psychiatry, 2026)
Abstract Objective Over one million Chinese international students (CIS) are currently enrolled in higher education abroad, predominantly in Western universities. The volume of research on CIS mental health has increased steadily in recent years, with evidence indicating poorer outcomes compared to both domestic and other international student groups. However, comprehensive syntheses and understanding of this literature remain limited. We conducted a scoping review to map the evidence on CIS mental health in Western higher education settings, to examine the strength and gaps of the evidence base, and to inform future research and support provision. Methods Based on a pre-registered strategy, we systematically searched MEDLINE, PsycINFO, Embase, ERIC, and CINAHL from inception to 10 December 2025. Grey literature was also searched (including PsycEXTRA, BASE, medRxiv, and PsyArXiv). Articles were reviewed for inclusion/exclusion by 2 authors. Result This scoping review integrates findings from 225 reports, examining three core areas: the prevalence of mental health issues, existing interventions, and factors influencing mental health and psychological well-being. Depression, anxiety, and psychological stress are the most commonly reported concerns, though prevalence estimates vary substantially. While some interventions exist, they are narrow in scope and lack evidence for effectiveness at scale. Factors associated with variation in mental health and psychological wellbeing among CIS include academic stress, social isolation, language difficulties, cultural adjustment, and inadequate institutional support. Conclusion High-quality evidence on prevalence and intervention effectiveness remains limited. These findings underscore the need for more robust, culturally responsive support systems and interventions to address the mental health needs of CIS in Western higher education settings.